Muscle wasting in animal models of severe illness - Holecek, Milan (International journal of experimental pathology, 2012)
Muscle wasting is a serious complication of various clinical conditions that significantly worsens the prognosis of the illnesses. Clinically relevant models of muscle wasting are essential for understanding its pathogenesis and for selective preclinical testing of potential therapeutic agents. The data presented here indicate that muscle wasting has been well characterized in rat models of sepsis (endotoxaemia, and caecal ligation and puncture), in rat models of chronic renal failure (partial nephrectomy), in animal models of intensive care unit patients (corticosteroid treatment combined with peripheral denervation or with administration of neuromuscular blocking drugs) and in murine and rat models of cancer (tumour cell transplantation). There is a need to explore genetically engineered mouse models of cancer. The degree of protein degradation in skeletal muscle is not well characterized in animal models of liver cirrhosis, chronic heart failure and chronic obstructive pulmonary disease. The major difficulties with all models are standardization and high variation in disease progression and a lack of reflection of clinical reality in some of the models. The translation of the information obtained by using these models to clinical practice may be problematic.
Keywords: Rats; zvířata; Wasting Syndrome; svalová atrofie; myši; Mice; Muscular Atrophy; syndrom chřadnutí; proteolýza; kosterní svaly; Muscle, Skeletal; Neoplasms; nádory; Sepsis; Animals; modely nemocí na zvířatech; sepse; Proteolysis; krysa rodu Rattus; Disease Models, Animal